On a novel dihalocyclopropane– dihalomethylvinyl rearrangement:Additional mechanistic evidence. Issue 5 (2005) - Jankowski Jankowski, Christopher K. Christopher K.; BouLaouz BouLaouz, Antoun Antoun; Diaz-Torres Diaz-Torres, Eduardo Eduardo
Abstract : Some additional evidences on the mechanism of new rearrangment of dihalocyclopropane–dihalomethylvinyl reaction assisted by Hiyama reagent Cr +2 /Cr +3 are discussed.